2023
DOI: 10.1038/s41467-023-38867-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential intrahost evolution and onward transmission of SARS-CoV-2 variants

Abstract: Persistent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections have been reported in immune-compromised individuals and people undergoing immune-modulatory treatments. Although intrahost evolution has been documented, direct evidence of subsequent transmission and continued stepwise adaptation is lacking. Here we describe sequential persistent SARS-CoV-2 infections in three individuals that led to the emergence, forward transmission, and continued evolution of a new Omicron sublineage, BA.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Each of these sites exhibits potential for evolution. For example, residues 455 and 456 show substantial amino acid variation across the sarbecovirus alignment, the Y453F mutation occurred independently in multiple outbreaks of SARS-CoV-2 in farms of American mink (Oude Munnink et al 2021; Ren et al 2021), and the mutation L455W has been observed in a chronic human SARS-CoV-2 infection (Gonzalez-Reiche et al 2023). At the time of writing, XBB.1.5 descendants such as EG.5 and XBB.1.16.6 (each containing F456L) and an EG.5 derivative that combines F456L with L455F (Pango lineage HK.3) have been detected, and in the case of EG.5.1 (containing F456L), begun to rise substantially in global frequency consistent with a selective advantage.…”
Section: Resultsmentioning
confidence: 99%
“…Each of these sites exhibits potential for evolution. For example, residues 455 and 456 show substantial amino acid variation across the sarbecovirus alignment, the Y453F mutation occurred independently in multiple outbreaks of SARS-CoV-2 in farms of American mink (Oude Munnink et al 2021; Ren et al 2021), and the mutation L455W has been observed in a chronic human SARS-CoV-2 infection (Gonzalez-Reiche et al 2023). At the time of writing, XBB.1.5 descendants such as EG.5 and XBB.1.16.6 (each containing F456L) and an EG.5 derivative that combines F456L with L455F (Pango lineage HK.3) have been detected, and in the case of EG.5.1 (containing F456L), begun to rise substantially in global frequency consistent with a selective advantage.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, insufficient polyclonal antibody reactivities have been described to induce the emergence of variants carrying multiple escape mutations [22, 27, 37], resulting in transmission [38]. Accordingly, the onset of the IgM antibody response in our patient six to seven weeks after infection was associated with the emergence of virus variants harbouring various additional mutations within the NTD and RBD of S. Of note, variants carrying substitutions and deletions at positions 140-4 and 241-3 of the NTD and substitution E484K within the RBD appeared, of which the triple mutant S:Delta141-4 E484K S494P became stably established until virus elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the strongest selective filter may occur upon transmission to new hosts (Xue et al, 2020, N’Guessan et al, 2023). In some cases, such as chronically infected patients, viral lineages that are selectively favored within a host can be transmitted to other hosts (Gonzalez-Reiche et al, 2023). As a result, within-host viral diversity may foreshadow the success of viral mutations and lineages at a global scale (Xue et al, 2017, Harari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have quantified and analyzed the level of intra-host diversity of SARS-CoV-2 in humans. Intra-host diversity of SARS-CoV-2 is generally low in acute human infections (Valesano et al, 2021, Lythgoe et al, 2021, Braun and Moreno et al, 2021), but much higher in chronic infections, during which mutations can be selected within a host and potentially transmitted to new hosts (Gonzalez-Reiche et al, 2023). In acute infections, the median number of intrahost single nucleotide variants (iSNVs) at measurable frequency has been estimated to be between one and eight (Lythgoe et al, 2021, Valesano et al, 2021), with most samples having fewer than three (Lythgoe et al, 2021) iSNVs.…”
Section: Introductionmentioning
confidence: 99%